Moxonidine and central alpha(2) adrenergic receptors in sodium intake - de Oliveira, L. B.; De Luca, L. A.; Menani, José Vanderlei [UNESP] (Elsevier B.V., 2003)
Central injections of the alpha(2) adrenergic/imidazoline receptor agonist moxonidine inhibit water and NaCl intake in rats. In the present study, we investigated the possible involvement of central alpha(2) adrenergic receptors on the inhibitory effect of moxonidine in 0.3 M NaCl intake induced by 24 h sodium depletion. Male Holtzman rats with stainless-steel cannulas implanted into the lateral ventricle (LV) were used. Sodium depletion was produced by the treatment with the diuretic furosemide (20 mg/kg of body weight) injected subcutaneously + 24 h of sodium-deficient diet. Intracerebroventricular (icv) injections of moxonidine (20 nmol/l mul) reduced sodium depletion-induced 0.3 M NaCl intake (6.6 +/- 1.9 ml/120 min vs. vehicle: 12.7 +/- 1.7 ml/120 min). Pre-treatment with the alpha(2) adrenoreceptor antagonists RX 821002 (80 nmol/l mul), SK&F 86466 (640 nmol/l mul) and yohimbine (320 nmol/3 mul) injected icv abolished the inhibitory effect of icv moxonidine on sodium depletion-induced 0.3 M NaCl intake (13.3 +/- 1.4, 15.7 +/- 1.7 and 11.8 +/- 2.2 ml/120 min, respectively). The results show that the activation of alpha(2) adrenoreceptors is essential for the inhibitory effect of central moxonidine on sodium depletion-induced NaCl intake. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: alpha(2) adrenergic and imidazoline receptors; salt appetite; electrolyte balance; sodium depletion; yohimbine; ingestive behavior